Analisis Keaktifan Siswa dalam Proses Pembelajaran Daring di Masa Pandemi COVID-19 - Al Halik; Zamratul Aini (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2020)
The goal of all learning efforts is for students to learn. In learning, students are subjects who are actively learning. Student success in learning is influenced by the quality of the student's activity. The purpose of this study was to determine the level of student activity in online learning during the Covid-19 pandemic from the aspects of visual activity, oral activity, listening activity, writing activity, emotional activity,and mental activity.This research Uses a descriptive quantitative approach. Data collection was carried out at two locations, namely the Vocational High School (SMK) and State Madrasah Aliyah (MAN) of 144 students. The instrument used to collect the data was a Scale of Students Active by Zamratul Aini, and questionnaires are distributed online through the Google Forms application. The results showed that in general the activeness of students in the online learning process was in the high category. The results of the research can be used as input for the counselor in planning, designing, implementing, and evaluating guidance and counseling programs according to the analysis of student needs. Besides, it can also serve as input for the Principal to provide support to implementers of guidance and counseling service activities. In its implementation, counselors need to collaborate with various parties, both school personnel and other parties outside the school, so that the success of these guidance and counseling services can be achieved optimally.